Development of swelling/floating gastroretentive drug delivery system based on a combination of hydroxyethyl cellulose and sodium carboxymethyl cellulose for Losartan and its clinical relevance in healthy volunteers with CYP2C9 polymorphism - Chen, Ray-Neng; Ho, Hsiu-O; Yu, Chiao-Ya; Sheu, Ming-Thau (European journal of pharmaceutical sciences, 2010)
The aim of this study was to develop an optimal gastroretentive drug delivery system (GRDDS) for administering Losartan. Additionally, the influence of optimized GRDDS on the bioavailability of Losartan and the formation extent of active metabolite E3174 by CYP2C9 polymorphism was investigated. Swellable and floatable GRDDS tablets combining hydroxyethyl cellulose (HEC), sodium carboxymethyl cellulose (NaCMC), and sodium bicarbonate were prepared at various compression pressures for evaluating swelling characteristics and floating capacity. Then Losartan was incorporated into optimized formulations for in vitro and in vivo characterizations. An appropriate ratio of HEC to NaCMC, addition of sodium bicarbonate, and compression at lower pressures resulted in the tablets floating over SGF for more than 16 h and swelling to 2 cm in diameter within 3 h. The release patterns of Losartan from these tablets were pH-dependent. Results of the clinical trials showed that the mean bioavailability from GRD-A (HEC 91.67%, sodium bicarbonate 3.33% and Losartan 8.33%) was approximately 164%, relative to the immediate-release product (Cozaar ®). MRT and t max values were greater and C max values were lower for the GRDDS tablets compared with Cozaar ®. The lower bioavailability of Losartan in the CYP2C9*1/*1 subjects than CYP2C9*1/*3 subjects was found and could be due to the variety of enzymatic activity.